THE ROLE OF SCIENCE AND ENLIGHTENMENT IN THE DEVELOPMENT OF PERSONAL SPIRITUAL QUALITIES - Suvonkulova Matluba Gulomjonovna (Scholar Express Journal, 2024)
In this article, the influence of science and enlightenment in ensuring the harmony of personality and its virtues is analyzed and conclusions are given in the appropriate order
Keywords: knowledge; wisdom; manners